ANALISIS RISIKO KESEHATAN LINGKUNGAN PAJANAN GAS KARBON MONOKSIDA (CO) PADA PETUGAS PENGUMPUL TOL DI SEMARANG - Devita Nur Aprilia; Nurjazuli Nurjazuli; Tri Joko (Jurnal Kesehatan Masyarakat (Undip), 2017)
Semarang has a toll way with a traffic growth rate of 6% per year. Since 2009 to 2013, there has been an increase in average daily vehicle traffic from 78.335 to 133.165 vehicles per day. Most of CO concentrations at four Semarang toll gates, Tembalang, Manyaran, Gayamsari and Muktiharjo toll gates, exceed the quality standard set by WHO and are close to the air quality standard specified in Decree of the Governor of Central Java Number 8 of 2001. The purpose of this study is to analyze the environmental health risks of Carbon Monoxide gas (CO) exposure to the toll collectors in Semarang. The type of this research is a Cross Sectional study with Environmental Health Risk Analysis method (ARKL). The subject sample of this study was the toll collectors who have worked for more than one year, while the object sample was the concentration of CO gas in toll collecting booth at each toll gate. The results showed that the concentration of Carbon Monoxide gas (CO) in ambient air of Semarang toll booths ranged from 3.45 mg/m3 up to 26.97 mg/m3, with an average of 10.61 mg/m3. The average of exposure time was 8 hours, with the frequency of exposure was 264 days, and the duration of exposure was 15.5 years. The calculation of individual risk values to the toll collectors showed the value of RQ <1 for real-time and lifetime exposure. The conclusion of this study was that the average concentration of CO was below the standards. The risk of Carbon Monoxide gas (CO) exposure in present (realtime) and in 30 years (lifetime) has not shown a risk of non carcinogenic.